2022
DOI: 10.2147/cia.s361459
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol, Nesfatin-1, and IL-1β: Potential Diagnostic Biomarkers in Elderly Patients with Treatment-Resistant Depression

Abstract: Aim Treatment-resistant depression (TRD) affects approximately 30% of patients with major depressive disorder (MDD), especially elderly patients. As individuals with TRD are at an increased risk of committing suicide and pose a higher risk of relapse, early diagnostic biomarkers of TRD and a better understanding of the resistance mechanism are highly needed. This study aimed to determine whether serum cortisol, nesfatin-1, and pro-inflammatory cytokines can be used as biomarkers for the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Sanchez-Carro et al ( 55 ) provided data supporting the role of TNF-α in discriminating between TRD and HC using a machine learning approach. These findings were replicated in a case–control cross-sectional study on elderly TRD patients, where TNF-α levels were significantly higher in TRD than in the HC group ( 65 ). In addition, in a double-blind, randomized, placebo-controlled trial, Strawbridge et al ( 59 ) found that the baseline pro-inflammatory proteins, including TNF-α, were significantly higher in TRD patients than in HC, after controlling for gender, age, childhood adversity and BMI.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Sanchez-Carro et al ( 55 ) provided data supporting the role of TNF-α in discriminating between TRD and HC using a machine learning approach. These findings were replicated in a case–control cross-sectional study on elderly TRD patients, where TNF-α levels were significantly higher in TRD than in the HC group ( 65 ). In addition, in a double-blind, randomized, placebo-controlled trial, Strawbridge et al ( 59 ) found that the baseline pro-inflammatory proteins, including TNF-α, were significantly higher in TRD patients than in HC, after controlling for gender, age, childhood adversity and BMI.…”
Section: Resultsmentioning
confidence: 67%
“…With respect to IL-1, available data are still inconsistent. In fact, while Uint et al ( 62 ) found higher IL-1b plasma levels in TRD compared to HC, Zincir et al ( 67 ) and Wu et al ( 65 ) found lower IL-1b levels of in TRD patients.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Serum cortisol, nesfatin-1 and IL-beta have been diagnostic biomarkers in elderly patients with treatment -resistant depression [8]. The stimulation of the HPA axis and over secretion of cortisol contributes to neurodegeneration which is a significant risk for late life depression and cognitive decline [41].…”
Section: Inflammation and Its Biomarkersmentioning
confidence: 99%
“…In a sample of community-dwelling adults older than 60 in China (N=4103), for example, 9% were noted to have comorbid depression and anxiety [7]. And, treatment resistant depression has been reported in as many as 30% of older patients with depression in another sample from China [8].…”
mentioning
confidence: 99%